Fixed-term contract positions, unemployment and mental ill health: a Danish cohort study - Harald Hannerz; Hermann Burr; Helle Soll-Johanning; Martin Lindhardt Nielsen; Anne Helene Garde; Mari-Ann Flyvholm (BMC, 2022)
Abstract Background Both perceived job insecurity and unemployment has been associated with an increased risk of developing mental ill health. It has, moreover, been proposed that an insecure employment may be as detrimental as unemployment itself. Objective To estimate incidence rate ratios (RRs) of (i) redeemed prescriptions for psychotropic drugs and (ii) psychiatric hospital treatment due to mood, anxiety, or stress-related disease, among fixed-term contract workers (as an operationalization of insecure job) vs. unemployed, in the general population of Denmark. Methods Data on baseline employment status were drawn from the Danish Labor Force Surveys in the years 2001-2013. Participants (10,265 fixed-term contract workers and 7926 unemployed) were followed for up to 5 years in national registers (2439 cases of psychotropic drug use, 71,516 person years; 311 cases of psychiatric hospital treatment, 86,790 person years). Adjusted RRs were obtained by Poisson regression. We aspired to minimize health selection effects by (i) exclusion of survey participants who received sickness benefits, social security cash benefits, psychiatric hospital treatment or a prescription for psychotropic drugs, within 1-year prior to baseline (n = 11,693), (ii) adjustment for age, gender, level of education, calendar year, disposable family income and maternity/paternity benefits within 1-year prior to baseline. Results The adjusted RR for fixed-term contract workers vs. unemployed was 0.98 (99.5% CI: 0.87-1.11) for psychotropic drugs and 0.93 (99.5% CI: 0.67-1.30) for psychiatric hospital treatment. Conclusion The present study did not find significant differences in the risk of developing mental ill health between fixed-term contract workers and unemployed, and thus suggests that fixed-term contracts may be as detrimental as unemployment. Trial registration International Registered Report Identifier (IRRID): DERR2-10.2196/24392.